Adherence to the dietary approaches to stop hypertension diet and all-cause mortality in patients with a history of heart failure - Chou, Ting-Yu; Liu, Wei-Ju; Lee, Chia-Lin; Wang, Jun-Sing (Frontiers in Nutrition, 2022)
Background and aims We investigated the association of adherence to the Dietary Approaches to Stop Hypertension (DASH) diet with all-cause mortality in patients with a history of heart failure. Methods We analyzed data from the National Health and Nutrition Examination Survey (NHANES). Dietary information was obtained from a 24-h dietary recall interview. Adherence to the DASH diet was assessed using the DASH score. The primary outcome was all-cause mortality which was confirmed by the end of 2011. Weighted Cox proportional hazards regression models were used to determine the hazard ratios and 95% CI for the association of the DASH score and all-cause mortality with multivariate adjustment. Results The median DASH score was 2 among the 832 study participants. There were 319 participants who died after a median follow-up duration of 4.7 years. A higher DASH score (>2 vs. ≤ 2) was not associated with a decrease in the risk of all-cause mortality (adjusted HR 1.003, 95% CI 0.760–1.323, p = 0.983). With respect to the components of the DASH score, a lower sodium intake was not associated with a decreased risk of mortality (adjusted HR 1.045, 95% CI 0.738–1.478, p = 0.803). Conclusion A higher DASH score (>2 vs. ≤ 2) was not associated with all-cause mortality in patients with heart failure.